Separate schools - divided community: The role of school in post-war social reconstruction - Čorkalo Biruški, Dinka (Array, 2007)
The experiences of post-conflict societies show that they continue to live with communities that are deeply divided. This process is especially difficult in communities such as the town of Vukovar, where two ethnic groups live in the same town, but lead practically parallel lives, and have virtually no mutual contacts. This division is evident in all aspects of social life, including the area of schooling. The children in Vukovar attend separate classes divided according to ethnicity, and the curriculum is provided either in the Croatian or in the Serbian language. In this way the basic condition for normalization of the inter-group relations – contact – is discouraged. Everyday normal contact, based on reciprocity and equal status, enabling children to meet their peers from the other group and to form close relations and friendships is almost nonexistent. In order to examine more thoroughly what kind of education Vukovar children, their parents and their teachers want and how they see the possibility of children from different ethnic backgrounds attending the same schools, we conducted an explorative study, asking 718 pupils attending elementary and high schools, 953 of their parents and 113 teachers of Croatian and Serbian origin about their attitudes towards their present and future education. We asked them about their attitudes towards separated and integrated schooling, about social integration of ethnic communities living in Vukovar, their attitudes towards minority assimilation and towards multiculturalism. These attitudes were then related with the measures of inter-ethnic relations: the type of inter-ethnic contacts and friendships and the tendency to discriminate against the out-group. This helped to identify social consequences that the present separated schooling has had on the interethnic attitudes and behaviors. The possibility of schools serving as an integrative social factor in the post-conflict society is discussed.